Training of environmental skills for 12th grade students, with application in the local horizon of the Nistru river on the Anenii Noi district sector - Igor CODREANU; Olesea IOVITA (Acta et Commentationes, Sciences of Education, 2022)
The article reflects methodological and practical aspects of training environmental / ecological skills of students in the 12th grade of LT ,,Olimp”, Puhăceni village, Anenii Noi district. The content refers to the normative requirements of the national curriculum in Geography, highlighted as specific competencies. These competencies are developed not only by studying the content of the textbook for the 12th grade and school atlases as teaching materials, but also by studying some legislative acts, an example being Law no. 440 of 27.04.1995, regarding the areas and strips for the protection of river waters and water basins. The consolidation of environmental / ecological competence was achieved through research in the local horizon in the protected area of ​​the Dniester River, through visual analysis and assessment of environmental components in relation to the articles of law studied. The students participated in several activities related to the sanitation and arrangement of the researched territory, in informing and raising the awareness of local public authorities and the community members regarding the most obvious forms of negative impact on the environment.